Association between virtues and posttraumatic growth: preliminary evidence from a Chinese community sample after earthquakes - Duan,Wenjie; Guo,Pengfei (PeerJ, 2015)
Objective. Relationship, vitality, and conscientiousness are three fundamental virtues that have been recently identified as important individual differences to health, well being, and positive development. This cross-sectional study attempted to explore the relationship between the three constructs and post-traumatic growth (PTG) in three directions, including indirect trauma samples without post-traumatic stress disorder (PTSD), direct trauma samples without PTSD, and direct trauma samples with PTSD. Methods. A total of 340 community participants from Sichuan Province, Mainland China involved in the study, most of which experienced Wenchuan and Lushan Earthquake. Participants were required to complete the self-reported questionnaire packages at one time point for obtaining their scores on virtues (Chinese Virtues Questionnaire), PTSD (PTSD Checklist-Specific), and PTG (Post-traumatic Growth Inventory-Chinese). Results. Significant and positive correlations between the three virtues and PTG were identified (r = .39–.56; p < .01). Further regression analysis by stepwise method reveled that: in the indirect trauma samples, vitality explained 32% variance of PTG. In reference to the direct trauma sample without PTSD, both relationship and conscientiousness explained 32% variance of PTG, whereas in the direct trauma sample with PTSD, only conscientiousness accounted for 31% the variance in PTG. Conclusion.This cross-sectional investigation partly revealed the roles of different virtues in trauma context. Findings suggest important implications for strengths-based treatment.
Keywords: Post-traumatic growth; Trauma; Virtues; Relationship; Conscientiousness; Vitality